The promise of GaAs 200 in small-angle neutron scattering for higher resolution - Magerl, Andreas; Lemmel, H.; Appel, M.; Weißer, Matthias; Kretzer, U.; Zobel, M. (Journal of Applied Crystallography, 2024)
The Q resolution in Bonse-Hart double-crystal diffractometers is determined for a given Bragg angle by the value of the crystallographic structure factor. To date, the reflections Si 220 or Si 111 have been used exclusively in neutron scattering, which provide resolutions for triple-bounce crystals of about 2×10-5Å-1 (FWHM). The Darwin width of the GaAs 200 reflection is about a factor of 10 smaller, offering the possibility of a Q resolution of 2×10-6Å-1 provided crystals of sufficient quality are available. This article reports a feasibility study with single-bounce GaAs 200, yielding a Q resolution of 4.6×10-6Å-1, six times superior in comparison with a Si 220 setup.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Bonse-Hart diffractometer; GaAs 200; ultra-small-angle neutron diffraction; USANS